2019
DOI: 10.1016/j.redox.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 5-aminolevulinic acid–based photodynamic therapy against keloid compromised by downregulation of SIRT1-SIRT3-SOD2-mROS dependent autophagy pathway

Abstract: Keloids exhibit cancer-like properties without spontaneous regression and usually recur post excision. Although photodynamic therapy (PDT) is a promising treatment, details of the mechanisms remain to be elucidated. In this study, we investigated mechanisms involved in 5-Aminolevulinic Acid (5-ALA)–based PDT against keloid. Found that 5-ALA-PDT induced superoxide anion-dependent autophagic cell death. Application of autophagy inhibitor 3-Methyladenine (3-MA) significantly prevented the effect that 5-ALA-PDT in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 38 publications
2
44
2
Order By: Relevance
“…The redox homeostasis in mitochondria is tightly regulated by antioxidant enzymes such as SOD2 and glutathione peroxidase (Lu et al, 2017). It is well established that acetylation of SOD2 plays an important role in regulating its antioxidant activity (Liu et al, 2019). Yeast Sir2 protein and its homolog sirtuins in other prokaryotic and eukaryotic organisms belong to a class of protein deacetylases and ADP ribosylases with a highly conserved NAD + -binding core region (Schwer et al, 2002;Jin et al, 2009;Yi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The redox homeostasis in mitochondria is tightly regulated by antioxidant enzymes such as SOD2 and glutathione peroxidase (Lu et al, 2017). It is well established that acetylation of SOD2 plays an important role in regulating its antioxidant activity (Liu et al, 2019). Yeast Sir2 protein and its homolog sirtuins in other prokaryotic and eukaryotic organisms belong to a class of protein deacetylases and ADP ribosylases with a highly conserved NAD + -binding core region (Schwer et al, 2002;Jin et al, 2009;Yi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sirtuin 3 (SIRT3) is the main deacetylase in the mitochondria and serves as a critical mediator in metabolic regulation and antioxidant function [ 22 , 23 , 24 , 25 ]. SOD2, as one target protein of SIRT3, is regulated by SIRT3 via acetylation of lysine residues [ 26 , 27 ]. Transgenic mice with global SIRT3 overexpression improved endothelial dysfunction and attenuated vascular oxidative stress, while SIRT3 depletion promoted endothelial dysfunction and exacerbate vascular hypertrophy in hypertension [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, instead of oxidative stress, SIRT1 deficiency increased placental and fetal T‐SOD activity. A recent study also found that inhibiting SIRT1 increased the activity of SOD2 and reduced mitochondrial ROS production . These findings indicated that the SIRT1/PGC1α path way plays an important role in placental mitochondrial energy metabolism and oxidative stress, thereby potentially affecting nutrient transport from placenta to fetus.…”
Section: Discussionmentioning
confidence: 81%